Strategi Komunikasi BKM Al-Jihad Imam Nawawi dalam Mengembangkan Dakwah pada Masyarakat di Griya Martubung II Kelurahan Tangkahan Medan Labuhan - Hutajulu, Fardha Faradhisa; Muktarrudin, Muktarrudin; Ritonga, Elfi Yanti (Lembaga Yasin AlSys, 2024)
This research aims to determine the communication strategy of the Al-Jihad Imam Nawawi Mosque in developing da'wah among the community in Griya Martubung II, Tangkahan sub-district, Medan Labuhan. Bkm al-jihad imam nawawi activity program in developing da'wah among the community in Griya Martubung II, Tangkahan sub-district, Medan Labuhan. As well as obstacles to Bkm Al-Jihad Imam Nawawi in developing da'wah among the community in The data collection technique used in this research is by conducting in-depth interviews (deep interviews) and documentation. The results of the research found by researchers are as follows, (1) The strategy of Bkm al-Jihad Imam Nawawi in developing da'wah among the community in Griya Martubung II, Tangkahan Medan Labuhan sub-district is a persuasive strategy. A persuasive strategy is a way to persuade and invite Mad'u to study Islamic teachings. (2) Bkm al-jihad imam nawawi's activity program in developing da'wah among the community in Griya Martubung II, Tangkahan sub-district, Medan Labuhan is by carrying out Islamic activities such as recitation, counseling and friendship. (3) The obstacles for Bkm al-Jihad Imam Nawawi in developing da'wah to the community in Griya Martubung II, Tangkahan Medan Labuhan sub-district are the lack of funds which resulted in the construction of the mosque being delayed compared to previous plans, and the lack of public awareness in studying the Islamic religion.